An interactive writing monitoring system for kids - Saraswat S.; Gupta H.P.; Dutta T. (My University, 2025)
Recent advances in sensor technology have led to increased research in the writing activity monitoring system. The main aim of the exiting work is to identify the pattern written by the user without considering the related context such as grip and orientation of the pencil. In our work, we develop an interactive writing monitoring system for kids that uses minimum sensors to recognize orientation and grip of the pencil, kids posture while writing, and continuous monitoring of writing activity. Live sensor readings from the pencil along with the collected context information such as posture of the kid, can be utilized for determining the orientation, grip position of the pencil, and symbols written by the kids. We developed an early prototype of the proposed system using accelerometer and pressure sensor for extracting the writing activities. Results of developed prototype are promising. As part of our future work, we aim at extending the developed system for multiple users, different writing activities, and improving the energy efficiency of the system. © 2018 IEEE.